Overview of status and conservation of Bengal florican Houbaropsis bengalensis in Nepal - Inskipp, Carol; Poudyal, Laxman Prasad; Chaudhary, Dhan Bahadur; Shahi, Ram; Baral, Hem Sagar (Nepalese Journal of Zoology, 2024)
Bengal florican Houbaropsis bengalensis is a globally Critically Endangered bustard species found in South and Southeast Asia. In Nepal it is rare, local and declining, and only breeds in three disjunct protected areas in the lowlands: Shuklaphanta and Chitwan National Parks (NPs), and Koshi Tappu Wildlife Reserve and adjoining areas. Declines of Bengal florican in all these protected areas are well documented. Populations decreased by 93% in Shuklaphanta NP between 1982 and 2024; by 75% in Chitwan NP between 1982 and 2023, and by 55% in Koshi Tappu Wildlife Reserve and adjoining areas between 2012 and 2022. The Nepal population is now considered to be less than 100 birds. The species formerly bred in Bardia NP but has not been recorded there since 2010. Koshi Tappu Wildlife Reserve and surrounding areas now support by far the largest population in Nepal. The best habitats for the species in the breeding season comprise areas of short grassland dominated by Imperata cylindrica where the birds can forage in the early mornings and evenings, interspersed with patches of taller grassland for concealment and nesting. Reasons for the species’ decline in the breeding season are thought to be inappropriate grassland management, especially burning when the birds have started nesting, disturbance, and encroachment of some grasslands by woody vegetation. Outside the breeding season, when the Bengal florican moves from protected areas into nearby unprotected farmlands, the species is further at risk from hunting, trapping, pesticide poisoning and disturbance. We recommend improving grassland management, working with local communities, encouraging multi-season crops in nearby farmlands which are less intensive and less disturbing for Bengal florican, raising conservation awareness with stakeholders, and regular monitoring.